Labor Reallocation, Employment, and Earnings: Vector Autoregression Evidence. (21st April 2019) - Hyatt, Henry R.; McElroy, Tucker S.
Abstract: We present time series evidence for the USA 1993–2013 on the relationship between labor reallocation, employment, and earnings using a vector autoregression framework. We find that an increase in labor market churn by 1 percentage point predicts that employment will increase by 100, 000–560, 000 jobs, lowering the unemployment rate by 0.05–0.25 percentage points. Job destruction does not predict changes in employment but a 1 percentage point increase in job destruction leads to an increase in unemployment 0.14–0.42 percentage points. We find mixed results on the relationship between labor reallocation rates and earnings.